Efektivitas Teknik Conseling Behavior Therapy (CBT) Untuk Mengatasi Kecemasan Sosial pada Kelas XI Shoshum 1 di SMA Negeri Ambulu - Sholehah, Elsa fitriatus; Rahmawati, Weni Kurnia; Fauziyah, Nailul (LPPM Institut Pendidikan Nusantara Global, 2025)
Social anxiety is one of the psychological disorders commonly experienced by adolescents, especially high school students, and can affect self-confidence, social relationships, and academic performance. This condition needs to be addressed through appropriate counseling interventions within the school setting. This study aims to determine the effectiveness of Cognitive Behaviour Therapy (CBT) counseling techniques in reducing social anxiety among 11th-grade students at SMA Negeri Ambulu. CBT was selected as it focuses on cognitive restructuring and modifying negative behaviors underlying anxiety. The study uses a quantitative approach with a quasi-experimental method, involving an experimental group and a control group. The instrument used is a social anxiety questionnaire developed based on the theories of Aaron T. Beck and La Greca. The results of this research are expected to contribute to the development of effective psychological interventions for students in schools.